The relative age effect in FIFA U-17 World Cup: The role of the playing position and the continent - ALI IŞIN; TUBA MELEKOĞLU (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: The aim of this study was to examine the relative age effect of the countries which attended the 2017 FIFA U-17 World Cup and to research the relative age effect in terms of continents and the players' position. Material and methods: 504 male football players from 24 countries which participated in the U-17 World Cup in India in 2017 were included in the study. Football players' dates of birth were grouped into periods of three months in quarter years (Q): Q1 - January-March, Q2 - April-June, Q3 - July-September, Q4 - October-December. To study the sub-group differences of the relative age effect, meaningful chi-square (χ²) values were followed by calculating the odds ratio and %95 confidence intervals. To determine the effect size, Cramer's V was used. Results: The relative age effect was based on quarter years' distributions. Significant differences were found among age quartiles for all teams in FIFA U-17 World Cup. However, when the variables analysed were according to the continents, the relative age effect disappeared in Africa, Asia and Oceania. Conclusions: In the comparison of the players' continents, a relative age effect was observed in Europe, North America, and South America. When the players' positions are compared, a relative age effect was found in defenders, midfielders and forward players.